USA TODAY EDITORIAL AND BUREAU OF NATL AFFAIRS BNA REPORT ON WORKPLACE SMOKING - AVEDON, DIANA (Tufts Archival Research Center, 2007)
Confidential; Missing Attachments; Memorandum from Diana Avedon to the Tobacco Institute Legislative council and the regional vice-presidents regarding a recent USA Today article and Bureau of National Affairs (BNA) report. Reports that one article calls restricting smoking in public places unrealistic. Mentions the BNA report stating that smokers’ rights should be considered.